2018
DOI: 10.1039/c8ra03298j
|View full text |Cite
|
Sign up to set email alerts
|

Upconversion from fluorophosphate glasses prepared with NaYF4:Er3+,Yb3+ nanocrystals

Abstract: The direct doping method was applied to fabricate upconverter fluorophosphate glasses in the system (90NaPO 3 -(10-x)Na 2 O-xNaF) (mol%) by adding ,Yb 3+ nanocrystals-containing glasses was observed using a 980 nm pumping, the intensity of which depends on the glass composition and on the direct doping parameters (T doping and dwell time). The strongest upconversion was obtained from the glass with x ¼ 10 prepared using a T doping of 550 C and a 3 min dwell time. Finally, we showed that the upconversion, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Additionally, the Er 3+ : 4 I 13/2 lifetime depends on the glass composition: independently of the particles, the Er 3+ : 4 I 13/2 lifetimes of the NaPF10 glasses are the shortest, thus suggesting that the particles are less degraded in the NaPF10 glass than in the NaPF0 one. Similar results were reported in Reference [25].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, the Er 3+ : 4 I 13/2 lifetime depends on the glass composition: independently of the particles, the Er 3+ : 4 I 13/2 lifetimes of the NaPF10 glasses are the shortest, thus suggesting that the particles are less degraded in the NaPF10 glass than in the NaPF0 one. Similar results were reported in Reference [25].…”
Section: Resultssupporting
confidence: 93%
“…In order to limit the degradation of the particles during the glass preparation, new glasses with a lower melting temperature and with a composition of 90NaPO 3 -(10 − x)Na 2 O-xNaF, with x = 0 (NaPF0) and 10 (NaPF10) (in mol %), were investigated as an alternative host for the Er 2 O 3 -doped particles. The optimization of the direct doping method can be found in Reference [25]; the Er 2 O 3 -doped particles were added at 550 °C and the dwell time was 3 min. As opposed to the NaSrP glasses, the Er 2 O 3 -doped TiO 2 - and ZnO-containing glasses exhibited a light pink coloration, whereas the Er 2 O 3 -doped ZrO 2 -containing glasses were colorless.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…d) Adapted with permission 67b. Copyright 2018, Elsevier B.V. e) Adapted with permission 65a. Copyright 2018, Royal Society of Chemistry.…”
Section: Methodology Of Embedding Nps Into a Glass Matrixmentioning
confidence: 99%
“…More recently, Petit's group has investigated the dissolution behavior of oxide PersL‐MPs and fluoride UCNPs in phosphate glasses with different compositions 65,67b,d. They found that, using the same doping temperature and dwell duration, Sr 4 Al 14 O 25 :Eu 2+ ,Dy 3+ particles (oxide PersL‐MPs) were prone to be dissolved to a larger extent by 90NaPO 3 –10NaF glass melt compared to 90NaPO 3 –10Na 2 O glass melt 67b.…”
Section: Methodology Of Embedding Nps Into a Glass Matrixmentioning
confidence: 99%